PROBLEMATIC ISSUES OF MEDICAL EXAMINATION OF YOUTH OF MILITARY AGE IN CONNECTION WITH STOMATOLOGIC PATHOLOGY - A. K. Iordanishvili; L. N. Soldatova (Кубанский научный медицинский вестник, 2016)
The frequency of occurrence is studied. The characteristic of the main dentoalveolar anomalies at recruits (entrants) and cadets of the highest military educational institutions taking into account features of medical examination of citizens at initial statement on the military account and military draft is submitted. Defects of work of the military-medical commissions of the young people who are carrying out examination preparing for entering in the HMEI are shown. The existing difficulties in ensuring the orthodontic help in conditions of military service are noted. The conclusion is drawn on need of the solution of problems of examination of young people at initial statement on the military account and military draft. It's drawn in connection with dentoalveolar anomalies which are available for them which demand specification, as in the medical, and legal plan.